Frecuencia de Neoplasias en Cavidad Oral de Caninos y Felinos, Diagnosticadas Histopatológicamente en el Laboratorio de Patología Veterinaria de la Universidad Nacional Mayor de San Marcos (Periodo 2007- 2013) - Páucar P., Jhessenia (2017)
The aim of this retrospective study was to determine the frequency of neoplasms in the oral cavity in canines and felines that were histopathologically diagnosed in the Veterinary Pathology Laboratory of the National University of San Marcos, Lima, Peru, in the period 2007 to 2013. A total of 115 cases of oral tumors were diagnosed in 1454 cases of canine tumors (7.9%) and 7 cases of oral tumors in 54 cases of feline tumors (13%). The epuli was the most frequent neoplasia (20.5%).